"Intervención didáctica" familiarización y encantamiento con la matemática (Educational Perspectives Magazine (REPED), 2022)
The high school Nonato Coo located at Puente Alto, Santiago Municipal, is the only municipal establishments on the sector that has no pre-school education level; therefore it receives students from different educational establishments, making it impossible to predict each student quality leaming, in important areas such as mathematics education.It should be noted that all schools in the municipality have the implementation of the educational program “Mathematics Their Way” written by the American educator Mary Baratía Lorton in the 70s, and is being released by the Fundación Astoreca, which aims at developing an educational program of mathematics for low-income children, based on an active methodology that uses the game as a source of leaming, using types of resources cióse to children (drawing games).This program is being implemented in all municipal schools in the first and second level of transition, and is overseen by the “Corporación Municipal de Educación de Puente alto” (Educational Corporation of Puente Alto). From this, high school Nonato Coo assumed as a weakness not to have students with prior experíence significant leaming about this program. Because of this reality was necessary doing a pedagogical intervention in 2008, addressed to first year “A” Basic high school education Nonato Coo which was in charge of their head teacher Juanita Morales, course consi sting of 22 students and 19 students. Ages corresponded to: 19 students with 6 years, 21 with 7 years and 1 student with 8 years making a total of 41 students. Regarding the organization of this project, we worked with guardián, who manufactures with recyclable materials didactic materials; they also were trained in the use and application of the material. That way, as the family is included inthe daily classroom teaching, in a participatory manner and committed. Regarding the educational space, was used the classroom, where twice a week so it would be organized according to the theoretical foundations of the pedagogical intervention.Throughout the year 2008, 8 authorized guardián participated actively assume their leading role to assist the leaming process that support the development of logical mathematical leamers. The attitude of the students was a great motivation and interest in the area of mathematics education, particularly in relation to direct experíence with concrete material and a different altemative to the traditional space and front.This year a math workshop room was created, which has been implemented with a range of recyclable materials, as both sets of mies and geometry resources purchased through the SEP, as well as boards of different textures (magnetic, cover floor, traditional and down). It is relevant that is currently used by students in First grade, Second and Fourth Basic, who along with there teacher workshop leader and teacher reinforce and feed off their own leaming of mathematics, with great emphasis on geometry.
Keywords: Intervention Education, Skills Development Thmking, Mathematical Logic